PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI TAMAN WISATA SELECTA BATU MALANG - -, Budi Prawoto (Manajemen & Bisnis Jurnal, 2015)
Abstract. The competitive advantage of an organization in today's global era is dependent primarily on how human resources (HR) in the organization is managed. The resources owned by the organization can not provide optimum results if not supported by human resources that have performance optimum.Tujuan this study to determine the effect simultaneously, partially dominant organizational culture, compensation and job satisfaction to employee performance Taman Batu Selecta .Populasi in this study were all employees of Parks Batuyang Selecta amounted to 41 employees. The sampling method sampling saturated, where all members of the population used as sampel.Hasil study showed that simultaneous and partial organizational culture, compensation and job satisfaction affect the performance of park employees Selecta Batu. While compensation is the dominant variable affecting the performance of research that is pegawai.Saran agencies in this regard Taman Batu Selecta Malangdiharapkan can improve job satisfaction which has always provided support and leadership of their promotions and rewards for employees who excel Keywords: organizational culture, compensation, job satisfaction and employee performance